2013
DOI: 10.1103/physrevb.88.235207
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation spectroscopy of excitons in ZnO

Abstract: Nonlinear optics of semiconductors is an important field of fundamental and applied research, but surprisingly the role of excitons in the coherent processes leading to harmonics generation has remained essentially unexplored. Here we report results of a comprehensive experimental and theoretical study of the three-photon process of optical second harmonic generation (SHG) involving the exciton resonances of the noncentrosymmetric hexagonal wide-band-gap semiconductor ZnO in the photon energy range of 3.2 − 3.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 66 publications
(85 reference statements)
4
78
0
11
Order By: Relevance
“…The latter 2Ω response corresponds to the SHG. It is experimentally shown that the excitons can contribute to the optical rectification [19,20] and the SHG [21][22][23]. While the optical rectification and the SHG are well-known nonlinear optical effects, their enhancement due to the exciton resonance has not been fully explored from the viewpoint of topology and geometry of the Bloch electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The latter 2Ω response corresponds to the SHG. It is experimentally shown that the excitons can contribute to the optical rectification [19,20] and the SHG [21][22][23]. While the optical rectification and the SHG are well-known nonlinear optical effects, their enhancement due to the exciton resonance has not been fully explored from the viewpoint of topology and geometry of the Bloch electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the nonlinear optical phenomena are widely used for applied researches [6]. Meanwhile, frequency conversion processes play an important role in nonlinear optical phenomena such as second or higher order harmonics generations [7]. Owing to rich classical nonlinear dynamics of frequency doubling processes, the second harmonic generation (SHG) is analyzed in this study [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the optical transitions associated with the second order nonlinear processes, the parity selection rules are different for contributing electronic states from those in linear phenomena. 20 Therefore, when the electric quadrupole allowed transition processes are taken into account, then an n th order electric-dipole-forbidden process can be stronger than an (n + 1) th order electric dipole allowed process. In the present investigation we realize it for observing second order nonlinear susceptibilities for the ZnO QD structure.…”
Section: Introductionmentioning
confidence: 99%
“…4,20 The nonlinear optical properties are reported for different forms of ZnO such as single crystals, thin films, nanowires and nano-ribbons. 14 The enhancement of the nonlinear optical properties as compared to bulk counterpart is observed for thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation